Long term changes in sex ratio and reproductive effort in the Baltic herring (Clupea harengus membras) in the south-western archipelago of Finland - Elfving, Mikael (fi=Turun yliopisto|en=University of Turku|, 2017)
Baltic herring (Clupea harengus membras) is a pelagic fish species that belongs to the pelagic food webs as a predator and as a prey. Herring is a key species in Baltic Sea ecosystem and a valuable fish for the fish industry around the Baltic Sea area. Because of this, monitoring of the herring is necessary for managing the fisheries and to see how the environmental changes affect the herring populations and the Baltic Sea. In the present study, the aim was to examine the long-term developments in sex ratio and reproductive effort of males in the spawning shoals. The study material has been collected annually from the spawning sites of herring in the Airisto Inlet in 1984-2014. The data set includes individual measurements of about 38 000 herring and 1-38 samples taken randomly from the commercial trap net catches throughout the main spawning season (May –July). The sex ratio (Nr males/Nr females) in the spawning shoals was examined with Generalized Linear Mixed Models (GLIMMIX) for the annual trends and to find out the factors possibly affecting the sex ratio in the shoals (sampling procedure, environmental and stock variables). Gonadosomatic index (GSI), which was used as an indicator of the reproductive effort, was also examined with GLIMMIX, to provide additional information on the reproductive capacity of the population. The results of the study indicate clear changes in the sex ratio of the spawning herring population. Firstly, the population is changing towards a female dominance. Secondly, the reproductive effort (gonadosomatic index) of the herring has decreased in males for which the change has been significant in all age classes. It seems that the present environmental conditions in the Baltic Sea and the ongoing climate change affect more on males than in females. This may change the population structure so that there are much more females than males in the population. If this trend continues for a long time, there is a risk for decrease in the population size in the future because the reproduction effort decreases.